1991
DOI: 10.1038/jcbfm.1991.10
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Microcirculation in a New Model of Focal Laser-Induced Secondary Brain Damage

Abstract: Summary:To study the causes of spatial and temporal evolution of progressive neuroinjury in focal brain isch emia, models with consistent lesion topography are re quired. In such models, continuous monitoring of the mi crocirculation in a penumbral area undergoing progres sive damage could be possible. We used a fixed-pulse 0.0 s, 40 W) Nd-Y AG laser (NYL) to produced discrete brain lesions in rats and monitored the cerebral blood flow (CBF) with laser-Doppler flowmetry (LDF) in nonirradi ated areas directly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Since cerebral accumulation of indium (" 'In)-labeled platelets failed to decrease, the treatment effect was concluded to be independent of platelets. In a new focal model of laserinduced secondary brain damage in rats, where a regular penumbral zone of ischemia, BBB damage, and edema develops surrounding a core of irreversible cortical neuronal necrosis [83], PAF antagonist (BN 50739) improved the penumbral CBF and edema and ameliorated the delayed neuronal necrosis, which otherwise extended into the vulnerable CA 1 hippocampal area [84]. Neutrophil accumulation in areas undergoing secondary brain damage was also reduced.…”
Section: Models Of Focal Cerebral Ischemiamentioning
confidence: 99%
“…Since cerebral accumulation of indium (" 'In)-labeled platelets failed to decrease, the treatment effect was concluded to be independent of platelets. In a new focal model of laserinduced secondary brain damage in rats, where a regular penumbral zone of ischemia, BBB damage, and edema develops surrounding a core of irreversible cortical neuronal necrosis [83], PAF antagonist (BN 50739) improved the penumbral CBF and edema and ameliorated the delayed neuronal necrosis, which otherwise extended into the vulnerable CA 1 hippocampal area [84]. Neutrophil accumulation in areas undergoing secondary brain damage was also reduced.…”
Section: Models Of Focal Cerebral Ischemiamentioning
confidence: 99%
“…Inhibition of the early and delayed postischemic hypoperfusion by the PAF antagonist is in agreement with our previous observation demonstrating perturbation of the rabbit spinal cord microcirculation by exogenous PAF. 24 During postischemic hypoperfusion following forebrain ischemia in gerbils and in a new model of laser-induced focal penumbral microcirculatory failure in rats, 25 similar beneficial effects of PAF antagonism were demonstrated, but not in association with PAF production. 26 - 27 However, PAF levels comparable to our results have been detected in rat brain injured by chemically induced convulsions.…”
Section: Discussionmentioning
confidence: 90%
“…More recent findings indicate that any primary necrosis of brain parenchyma evolving from a focal traumatic insult is subject to secondary growth. A variety of experiments utilizing different trauma models in various species have consistently shown that the size of a focal tissue necrosis increases within 24 h. The observed "growth" has been reported between 130 and 400 % of the initial lesion (Eggert et al, 1985;Lindsberg et al, 1991;Vonhof, 1997;Wyrwich, 1997;Murakami et al, 1999). A study from our laboratory has followed the growth kinetics of a focal cortical lesion at 5 min, and 3, 6, 12, 18, and 24 h after freezing injury in the rat by means of histology (Eriskat et al, 1994).…”
Section: Introductionmentioning
confidence: 94%